Inferring Variation in Southern Elephant Seal At-Sea Mortality by Modelling Tag Failure - Henderson, Angus F.; McMahon, Clive R.; Harcourt, Rob; Guinet, Christophe; Picard, Baptiste; Wotherspoon, Simon; Hindell, Mark A. (Frontiers in Marine Science, 2020)
Identifying factors influencing survivorship is key to understanding population persistence. Although satellite telemetry is a powerful tool for studying remote animal ecology and behaviour it is rarely used for demographic studies because distinguishing the death of the animal (individual mortality) from failure of the tag (mechanical tag failure) has proven difficult. Southern elephant seals present an opportunity to separate tag failure from animal mortality thanks to the availability of large tracking datasets, broad knowledge of demographic rates, and because for these large animals, satellite tags are known not to influence mortality rates. A key rationale for investigating satellite telemetry to estimate mortality as compared to using traditional Capture-Mark-Recapture methods is the potential for obtaining spatially and temporally specific information, particularly while the animals are at sea and largely unobservable. We used satellite tag data from 182 seals from Isles Kerguelen, deployed between 2004 and 2018. Of these, 76 (42%) tags transmitted for the full post-moult foraging trip (max. 265 days for females and max. 305 days for sub-adult males) with the remaining 107 tags (58%) ceasing transmission at sea. We found that contrary to expectations, behavioural choices seem not to influence tag failure rates by mechanical means, rather the signals we detected seemed to align with previously described variation in mortality between groups. There was evidence, albeit limited, for an increase in tag failure for adult females in years with negative Southern Annular Mode (lower Southern Ocean productivity). We speculate that this increase in failure may suggest higher mortality in these years. Also, males using the Kerguelen Plateau had higher tag failure rates than those in the sea-ice zone, perhaps indicative of higher mortality. We suspect that these differences in tag failure rates between groups reflect variation in predator exposure and foraging success. This suggests satellite telemetry could be used to infer mortality events for southern elephant seals while they are at sea.